O livro dos Adynata: impossibilidades na poética de Myriam Fraga - Gois, Danielle Assis Santos (2019)
In O livro dos Adynata, Myriam Fraga translates the ceaseless struggle of the character by dissociating signs printed in the culture and inscribed in the female body as a counterpoint to what really makes sense to itself, or, in other terms, what makes it feel. The character shows confusion, agonies and anguishes, between the silencing and the speaking, to see and to not see and then, the union of the learnings about itself until the brink of being. The psychological aspects mix with the graphic plurality of Fraga’s poetry, and while we analyze her work, through the help of Antonio Candido, Norma Goldstein and Massaud Moises, we rely on Alfredo Bosi, Roland Barthes, Theodor Adorno and Octavio Paz as main representatives of the studies of poetic writing and its ripples; the latter, were based on the psychoanalytic theory, since they create emotions on the readers, and in this case, were approached by Sigmund Freud and Jacques Lacan. Through the analysis of Fraga’s poetic it is intended to demonstrate that in the plurality of its signs and significations, the possibilities are beyond words.